Self-Monitoring With Secondary Students: Using a Smartphone App to Increase Attention to Task. (August 2022) - Cook, Kathleen B.; Sayeski, Kristin L.
Despite decades of robust evidence demonstrating the effectiveness of self-monitoring for attention, the strategy is not universally taught to students who struggle with attention, particularly within general education settings. Recent studies have included technology such as tablets or smartphones, adding to the ease and social acceptability of the self-monitoring strategy. In this article, we provide the steps and tips for teachers to use an inexpensive smartphone app to increase on-task attending during instruction.